Evolutionary biology - Futuyma, Douglas J.; Futuyma, Douglas J. (Sunderland, Massachusetts Sinauer Associates, 1998)
The third edition of this comprehensive book has increased its scope while emphasizing the intellectual order and molecular perspectives which have added to evolutionary studies in the 1990s.
Appendix I-II, 755-769p.; Glossary .; References.; Index .
Keywords: Evolutionary biology; Biology